The Role of Parents in Motivating Children to Participate in Qur'anic Learning at TPQ An-Nur - Persa Tri Siski; Izmi Ar-Rahma Donia; Ana Hasanah; Melsa Fadnecya Suhendar; Juwita Gustia Lestari; Mus Mulyadi (Yayasan Azhar Amanaa Yogyakarta, 2025)
This study aimed to analyze the role of parents in motivating children to participate in Qur'anic learning activities at TPQ An-Nur, Padang Tekurung IV, Betungan Subdistrict, Bengkulu City. The study employed a qualitative descriptive research design to explore parental involvement and factors influencing children's participation in religious learning activities. Research participants consisted of parents, TPQ teachers, mosque administrators, and elementary school students involved in TPQ activities. Data collection techniques included observation, interviews, and documentation, while data analysis was conducted through data reduction, data presentation, and conclusion drawing. The findings indicated that parents played important roles through emotional support, supervision, guidance, motivation, and educational assistance that encouraged children to participate actively in Qur'anic learning activities. Children's participation was also influenced by several supporting and inhibiting factors, including family support, learning motivation, teacher involvement, peer relationships, learning environments, educational facilities, and technological influences. Positive parental involvement contributed to increasing children's enthusiasm, discipline, and participation in learning activities. The study concludes that active parental roles and supportive educational environments are important factors in strengthening children's participation in Qur'anic learning activities and improving religious learning development.